Pyramiding PvPGIP2 and TAXI-III but not PvPGIP2 and PMEI enhances resistance against fusarium graminearum - Tundo, Silvio; Kalunke, Raviraj; Janni, Michela; Volpi, Chiara; Lionetti, Vincenzo; Bellincampi, Daniela; Favaron, Francesco; D'Ovidio, Renato (Molecular Plant-Microbe Interactions, 2016)
Plant protein inhibitors counteract the activity of cell wall degrading enzymes (CWDEs) secreted by pathogens to breach the plant cell-wall barrier. Transgenic plants expressing a single protein inhibitor restrict pathogen infections. However, since pathogens secrete a number of CWDEs at the onset of infection, we combined more inhibitors in a single wheat genotype to reinforce further the cell-wall barrier. We combined polygalacturonase (PG) inhibiting protein (PGIP) and pectin methyl esterase inhibitor (PMEI), both controlling the activity of PG, one of the first CWDEs secreted during infection. We also pyramided PGIP and TAXI-M, a xylanase inhibitor that controls the activity of xylanases, key factors for the degradation of xylan, a main component of cereal cell wall. We demonstrated that the pyramiding of PGIP and PMEI did not contribute to any further improvement of disease resistance. However, the presence of both pectinase inhibitors ensured a broader spectrum of disease resistance. Conversely, the PGIP and TAXI-HI combination contributed to further improvement of Fusarium head blight (FHB) resistance, probably because these inhibitors target the activity of different types of CWDEs, i.e., PGs and xylanases. Worth mentioning, the reduction of FHB symptoms is accompanied by a reduction of deoxynivalenol accumulation with a foreseen great benefit to human and animal health.

Detection of ciprofloxacin residues in cow milk: a novel and rapid optical beta-galactosidase-based screening assay - Kalunke, Raviraj M.; Grasso, Gerardo; D'Ovidio, Renato; Dragone, Roberto; Frazzoli, Chiara (Microchemical Journal, 2018)
Ciprofloxacin (a member of the fluoroquinolone class) is one of the most widely used antibacterial agents for the treatment of bacterial infections in livestock. The improper use of such antibacterial agents could lead to the presence of residues in animal origin foods (including milk) and consequently harmful effects for health of consumers, together with the spread of antibiotic-resistant bacterial strains. Therefore, in order to support good farming practices and to ensure food safety, antimicrobial (in particular fluoroquinolones) residues surveillance through improved monitoring techniques is crucial. However, commercial available kits for the detection of fluoroquinolones residues in food samples are time-consuming and still fail to detect MRL concentrations for fluoroquinolones (e.g. 0.1 mg/kg for the sum of enrofloxacin and ciprofloxacin residues). Here a novel and rapid assay for ciprofloxacin residual detection through optical microbiological screening in commercially pasteurized cow's milk samples is described. Escherichia coli ATCC 11303 cell proliferation was optically monitored by measuring endogenous (beta-gal activity that was determindd through colorimetric assay in the presence of a chromogenic beta-gal artificial substrate. Optical density of E. coli cell culture (linked to cell proliferation) was positively correlated with endogenous beta-gal activity. As the presence of ciprofloxacin residues inhibits the E. coli cell proliferation in tested samples, (3-gal levels decreased more in exposed samples than in control. The essential step of beta-gal induction (usually obtained by IPTG) was obtained by exploiting the lactose present in the milk. Our findings show a detection of ciprofloxacin residues at 1 MRL concentration after 1 h using ONPG as chromogenic 3 gal artificial substrate and lactose as (3-gal inducer. Compared to previously described methods, this assay proved to be a rapid, proficient and more eco-friendly (i.e. minimizing the use of additional reagents) system that could be potentially employed as screening method for detection ciprofloxacin residues in cow's milk. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Antibiotic resistance; Farm animals; Fluoroquinolones; HACCP; One health; Primary production; Risk assessment and management